Fragmented ECG as a Risk Marker in Cardiovascular Diseases - Jain, Rahul; Singh, Robin; Yamini, Sundermurthy; K. Das, Mithilesh (Current Cardiology Reviews, 2014)
Various noninvasive tests for risk stratification of sudden cardiac death (SCD) were studied, mostly in the context of structural heart disease such as coronary artery disease (CAD), cardiomyopathy and heart failure but have low positive predictive value for SCD. Fragmented QRS complexes (fQRS) on a 12-lead ECG is a marker of depolarization abnormality. fQRS include presence of various morphologies of the QRS wave with or without a Q wave and includes the presence of an additional R wave (R’) or notching in the nadir of the R’ (fragmentation) in two contiguous leads, corresponding to a major coronary artery territory. fQRS represents conduction delay from inhomogeneous activation of the ventricles due to myocardial scar. It has a high predictive value for myocardial scar and mortality in patients CAD. fQRS also predicts arrhythmic events and mortality in patients with implantable cardioverter defibrillator. It also signifies poor prognosis in patients with nonischemic cardiomyopathy, arrhythmogenic right ventricular cardiomyopathy and Brugada syndrome. However, fQRS is a nonspecific finding and its diagnostic prognostic should only be interpreted in the presence of pertinent clinical evidence and type of myocardial involvement (structural vs. structurally normal heart).
Keywords: coronary artery disease